Addressing coloniality of power to improve HIV care in South Africa and other LMIC - Ordóñez, Claudia E.; Marconi, Vincent C.; Manderson, Lenore (Frontiers in Reproductive Health, 2023)
We describe the appropriateness and potential for effectiveness of three strategic approaches for improving HIV care in South Africa: community-based primary healthcare, local/community-based stakeholder engagement, and community-engaged research. At their core, these approaches are related to overcoming health inequity and inequality resulting from coloniality of power's heterogenous structural processes impacting health care in many low- and middle-income countries (LMIC). We turn to South Africa, a middle-income country, as an example. There the HIV epidemic began in the 1980s and its ending is as elusive as achieving universal healthcare. Despite impressive achievements such as the antiretroviral treatment program (the largest in the world) and the country's outstanding cadre of HIV experts, healthcare workers and leaders, disadvantaged South Africans continue to experience disproportionate rates of HIV transmission. Innovation in global public health must prioritize overcoming the coloniality of power in LMIC, effected through the imposition of development and healthcare models conceived in high-income countries (HIC) and insufficient investment to address social determinants of health. We advocate for a paradigm shift in global health structures and financing to effectively respond to the HIV pandemic in LMIC. We propose ethically responsive, local/community-based stakeholder engagement as a key conceptual approach and strategy to improve HIV care in South Africa and elsewhere. We join in solidarity with local/community-based stakeholders' longstanding efforts and call upon others to change the current status quo characterized by global public health power concentrated in HIC.